2021
DOI: 10.3389/fcell.2021.661787
|View full text |Cite
|
Sign up to set email alerts
|

Back to the Future: From Appendage Development Toward Future Human Hair Follicle Neogenesis

Abstract: Hair disorders such as alopecia and hirsutism often impact the social and psychological well-being of an individual. This also holds true for patients with severe burns who have lost their hair follicles (HFs). HFs stimulate proper wound healing and prevent scar formation; thus, HF research can benefit numerous patients. Although hair development and hair disorders are intensively studied, human HF development has not been fully elucidated. Research on human fetal material is often subject to restrictions, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 122 publications
0
24
0
Order By: Relevance
“…Several intercellular signaling pathways are critical for initiating and patterning hair follicle development (Biggs & Mikkola, 2014; de Groot et al, 2021; Saxena et al, 2019). Hair follicle primordia contain high levels of WNT activity and are a source of FGFs, BMPs, BMP inhibitors, and TGFβ (de Groot et al, 2021). Fgf20 is expressed in primary ectodermal hair placodes prior to detectable markers of the dermal condensation (Huh et al, 2013).…”
Section: Selected Topics In Genetics Development Regeneration and Dis...mentioning
confidence: 99%
“…Several intercellular signaling pathways are critical for initiating and patterning hair follicle development (Biggs & Mikkola, 2014; de Groot et al, 2021; Saxena et al, 2019). Hair follicle primordia contain high levels of WNT activity and are a source of FGFs, BMPs, BMP inhibitors, and TGFβ (de Groot et al, 2021). Fgf20 is expressed in primary ectodermal hair placodes prior to detectable markers of the dermal condensation (Huh et al, 2013).…”
Section: Selected Topics In Genetics Development Regeneration and Dis...mentioning
confidence: 99%
“…The global gene expression analysis showed that the remodeling of the ECMs seen in in vivo hair follicles ( 48 ), including laminins, fibronectins, and collagens, was activated in the hair follicloids (Fig. 4B).…”
Section: Discussionmentioning
confidence: 99%
“…Spiny mice are notable for their ability to regenerate skin through non-lethal predation involving wound-induced hair neogenesis (WIHN). During WIHN, a progeny of interfollicular, epidermal, and dermal cells become “embryonic-like” to restore early epithelial-mesenchymal interactions, resulting in the regeneration of hair follicles, fat, and arrector pili muscles [ 53 ]. Interestingly, some find WIHN to be akin to the blastema formation that occurs in axolotls, for example, that may entail similar signaling regulatory networks.…”
Section: Skin Regeneration and Wound-induced Hair Neogenesismentioning
confidence: 99%